Processing of harmonics in the lateral belt of macaque auditory cortex - Kikuchi, Yukiko; Horwitz, Barry; Mishkin, Mortimer; Rauschecker, Josef P. (Frontiers in Neuroscience, 2014)
Many speech sounds and animal vocalizations contain components, referred to as complex tones, that consist of a fundamental frequency (F0) and higher harmonics. In this study we examined single-unit activity recorded in the core (A1) and lateral belt (LB) areas of auditory cortex in two rhesus monkeys as they listened to pure tones and pitch-shifted conspecific vocalizations (‘coos’). The latter consisted of complex-tone segments in which F0 was matched to a corresponding pure-tone stimulus. In both animals, neuronal latencies to pure-tone stimuli at the best frequency (BF) were ~10 to 15 ms longer in LB than in A1. This might be expected, since LB is considered to be at a hierarchically higher level than A1. On the other hand, the latency of LB responses to coos was ~10 to 20 ms shorter than to the corresponding pure-tone BF, suggesting facilitation in LB by the harmonics. This latency reduction by coos was not observed in A1, resulting in similar coo latencies in A1 and LB. Multi-peaked neurons were present in both A1 and LB; however, harmonically-related peaks were observed in LB for both early and late response components, whereas in A1 they were observed only for late components. Our results suggest that harmonic features, such as relationships between specific frequency intervals of communication calls, are processed at relatively early stages of the auditory cortical pathway, but preferentially in LB.